Assessment of leakage dose in vivo in patients undergoing radiotherapy for breast cancer. (January 2018) - Lonski, Peta; Kron, Tomas; Taylor, Michael; Phipps, Alicia; Franich, Rick; Chua, Boon
Abstract: Background and purpose: Accurate quantification of the relatively small radiation doses delivered to untargeted regions during breast irradiation in patients with breast cancer is of increasing clinical interest for the purpose of estimating long-term radiation-related risks. Out-of-field dose calculations from commercial planning systems however may be inaccurate which can impact estimates for long-term risks associated with treatment. This work compares calculated and measured dose out-of-field and explores the application of a correction for leakage radiation. Materials and methods: Dose calculations of a Boltzmann transport equation solver, pencil beam-type, and superposition-type algorithms from a commercial treatment planning system (TPS) were compared with in vivo thermoluminescent dosimetry (TLD) measurements conducted out-of-field on the contralateral chest at points corresponding to the thyroid, axilla and contralateral breast of eleven patients undergoing tangential beam radiotherapy for breast cancer. Results: Overall, the TPS was found to under-estimate doses at points distal to the radiation field edge with a modern linear Boltzmann transport equation solver providing the best estimates. Application of an additive correction for leakage (0.04% of central axis dose) improved correlation between the measured and calculated doses at points greater than 15 cm from the field edge. Conclusions: Application of a correction for leakage doses within peripheral regions is feasible and could improve accuracy of TPS in estimating out-of-field doses in breast radiotherapy.